In Vitro Regeneration of African Yam Bean (Sphenostylis stenocarpa (Hochst ex. A. Rich.) Harms by Direct Organogenesis - Adesoye, A.I.; Emese, A.; Olayode, O.M. (Agriculture and Natural Resources, 2012)
Studies on in vitro organogenesis of African yam bean (Sphenostylis stenocarpa) were carried out with the aim of developing a rapid regeneration system for this crop. Embryo and leaf explants were cultured on Murashige and Skoog (MS) containing varying concentrations and combinations of 6-benzyl aminopurine (BAP), kinetin and α-naphthalene acetic acid (NAA). The maximum number of shoots per explant (4.5) and percentage multiple shoot induction (100%) were obtained in MS supplemented with 0.05 mg.L-1 NAA and 0.5 mg.L-1 BAP. The maximum shoot length (135 mm) was obtained on a medium with 1.0 mg.L-1 kinetin and 0.1 mg.L-1 NAA. When cotyledonary node explants and shoot tip explants were cultured on media with BAP and kinetin singly, each at 1.0, 1.5 and 2.0 mg.L-1, both explants produced the maximum number of shoots (4.75) and shoot length (25 mm) on 2.0 mg.L-1 BAP while the least responses were obtained on 1.0 mg.L-1 kinetin. There was no organ formation from leaves as they all produced calli. Multiple shoots from the embryo produced roots directly on shoot induction medium while shoot tip-derived multiple shoots rooted when tested on both 0.25 and 0.5 mg.L-1 NAA. Shoots from cotyledonary nodes did not produce roots. Successfully rooted plantlets obtained from this study is the ﬁ rst report of in vitro plant regeneration in African yam bean. This procedure for direct organ differentiation would facilitate micropropagation and improvement of this species through genetic transformation.